2012
DOI: 10.1186/1477-7819-10-248
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted versus open D2 radical gastrectomy for advanced gastric cancer without serosal invasion: a case control study

Abstract: BackgroundThe application of laparoscopic surgery for advanced gastric cancer (AGC) remains questionable on account of technical difficulty of D2 lymphadenectomy, and there has been few large-scale follow-up results regarding the oncological adequacy of laparoscopic surgery compared with that of open surgeries for AGC. The aim of this study is to evaluate technical feasibility and oncological efficacy of laparoscopy-assisted gastrectomy (LAG) for advanced gastric cancer without serosal invasion.MethodsFrom Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
4
28
2
Order By: Relevance
“…As the technique has matured in recent years, some researchers have reported that not only was the overall number of lymph nodes that could be retrieved laparoscopically similar to that of laparotomy, but also that the specific lymph nodes such as No. 7, 8a, 9, 11p, 12a and 14v retrieved were also similar to that of laparotomy, which were once considered difficult to dissect under laparoscope 36,37.…”
Section: Discussionmentioning
confidence: 53%
“…As the technique has matured in recent years, some researchers have reported that not only was the overall number of lymph nodes that could be retrieved laparoscopically similar to that of laparotomy, but also that the specific lymph nodes such as No. 7, 8a, 9, 11p, 12a and 14v retrieved were also similar to that of laparotomy, which were once considered difficult to dissect under laparoscope 36,37.…”
Section: Discussionmentioning
confidence: 53%
“…They reported no statistical difference on rates of positive resection margins. Chen et al 21 concerning gastrectomy for advanced gastric cancers have shown similar surgical duration between laparoscopy and open resection. Blood loss and duration of hospital stay were signifi cantly less using laparoscopy for gastric resection.…”
Section: Discussionmentioning
confidence: 89%
“…Chen et al in 2012 (29) evaluated 224 patients who underwent LAG and 112 for the OG. The clinicopathological characteristics were similar as well as the number of lymph nodes of harvested (30.6 ± 10 vs. 30.3 ± 8.6 p = 0.786).…”
Section: Laparoscopic Assisted Gastrectomy For Advanced Gastric Cancermentioning
confidence: 99%
“…No difference was noted in the incidence of morbidity and mortality. Survival was similar for both groups (91.5% vs. 89.8% p > 0.05) (29). Hamabe (30) included 66 patient in the LAG and 101 in the OG.…”
Section: Laparoscopic Assisted Gastrectomy For Advanced Gastric Cancermentioning
confidence: 99%